Internalizing Panca Jiwa Values for Religious Moderation in Character Education at Wali Songo Ngabar Ponorogo - Ainus Sicha; A. Jauhar Fuad; M. Arif Khoiruddin; Izuli Dzulkifli (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study examines the internalization of Panca Jiwa values to foster religious moderation through character education at Wali Songo Ngabar Islamic Boarding School in Ponorogo. While previous studies have mainly examined moral development and disciplinary practices in pesantren-based character education, this study explores how Panca Jiwa values are experienced, practiced, and internalized in the daily lives of santri, shaping both their character and moderate religious attitudes. Using a qualitative phenomenological approach, data were collected through participant observation, in-depth interviews with pesantren leaders, teachers, administrators, and santri, and documentation. The credibility of the findings was strengthened through source triangulation and member checking. The findings show that the internalization of Panca Jiwa takes place through three interconnected processes: transformation, transaction, and transinternalization. These processes are reinforced through habituation, role modeling, and continuous interaction within the pesantren environment. The study concludes that Panca Jiwa functions as a moral foundation that supports character formation and nurtures religious moderation among santri. Theoretically, the findings contribute to a deeper understanding of how the internalization of pesantren values through transformation, transaction, and transinternalization can foster moderate religious character within the context of Islamic boarding school education.